The Effect of Using Ludo Boardsgames Learning Media on Students' Concept Understanding Ability - Simbolon, Marlina Eliyanti; Hermawati, Eli; Baharizqi, Sindi Ladya (International Conference on Elementary Education, 2022)
The problem in this study is the low understanding of students' concepts on science content which is under the KKM. This study aims to describe the differences in students' conceptual understanding in the experimental class who received the Ludo boardgames learning media and the control class who did not receive the Ludo boardgames learning media and to describe the differences in the improvement of students' conceptual understanding in the experimental class using the Ludo boardgames media and the control class that did not use the Ludo boardgames media. ludo boardgames learning media. This method uses the Quasi-Experimental method, while the research design uses the Nonequivalent Control Group Design. The dependent variable in this study is understanding the concept and the independent variable is the use of Ludo boardgames learning media. The research subjects were fifth grade students. The instrument used in this study was an essay test. The results showed that tcount > ttable. So that there are differences in students' understanding of concepts after being given treatment using the Ludo board games learning media. In addition, the difference in increasing understanding of the concept can be seen from the results of the t-gain test, the results of tcount> ttable. So that there is a difference in the increase (gain) of students' understanding of concepts using the Ludo boardgames learning media with those not using the Ludo boardgames learning media. The difference in increasing understanding of the concept can be seen from the results of the t-gain test, the results of tcount> ttable. So that there is a difference in the increase (gain) of students' understanding of concepts using the Ludo boardgames learning media with those not using the Ludo boardgames learning media. The difference in increasing understanding of the concept can be seen from the results of the t-gain test, the results of tcount> ttable. So that there is a difference in the increase (gain) of students' understanding of concepts using the Ludo boardgames learning media with those not using the Ludo boardgames learning media.